The Actin/Spectrin Membrane-Associated Periodic Skeleton in Neurons - Unsain, Nicolas; Stefani, Fernando D.; Cáceres, Alfredo (Frontiers in Synaptic Neuroscience, 2018)
Neurons are the most asymmetric cell types, their axons commonly extending thousand times the diameter of the cell soma. Fluorescence nanoscopy have recently unveiled that actin, spectrin and accompanying proteins form a membrane-associated periodic skeleton (MPS) that is ubiquitously present in mature axons from all neuronal types evaluated so far. The MPS is a regular supramolecular protein structure consisting of actin “rings” separated by spectrin tetramer “spacers”. Although the MPS is best organized in axons, it is also present in dendrites, dendritic spine necks and thin cellular extensions of non-neuronal cells, such as oligodendrocytes and microglia. The unique precise organization of the actin/spectrin skeleton has raised the hypothesis that it might serve to support the extreme physical and structural conditions that axons must resist during the lifespan of an organism. Other attempts to uncover the functionality of the MPS have focused on membrane domain organization. This review focuses on what we know so far on the structure of the MPS in different neuronal subdomains, its dynamics and the emerging evidence of its impact in axonal biology.